Efficacy of problem based learning approach for teaching evidence based practice in midwifery and nursing education: a systematic review - Komuhangi, Grace; Neuhann, Florian; Louis, Valérie R.; Ocan, Moses; Kinengyere, Alison Annet; Wacker, Jürgen (BMC nursing, 2025)
Background: Problem-Based Learning (PBL) has emerged as a promising strategy for teaching Evidence-Based Practice (EBP) to nursing and midwifery professionals. However, its effectiveness remains insufficiently synthesized, with few studies directly addressing its impact on EBP competencies. Objective: To systematically review and synthesize evidence on the efficacy of Problem-Based Learning as a teaching approach for developing Evidence-Based Practice competencies among nursing and midwifery students and professionals. Methods: This systematic review with narrative synthesis was conducted in accordance with the Cochrane Handbook and reported following PRISMA 2020 guidelines. The protocol was registered in PROSPERO (CRD42023390989). A comprehensive search of MEDLINE, CINAHL, PubMed, EMBASE, Web of Science, ERIC, PsycINFO, and Cochrane CENTRAL was performed from inception through August 2025. Two reviewers independently screened and appraised studies using JBI-SUMARI tools and ROBINS-I. Results: Eighteen studies met inclusion criteria, but only three (16.7%) specifically examined PBL for EBP education among nursing students in Iran, Japan, and South Korea. These consistently demonstrated significant improvements in knowledge, attitudes, critical thinking, and clinical decision-making compared with traditional methods, with all rated at low risk of bias. Broader EBP education studies reported highly variable implementation rates (13–100%), with higher educational levels linked to greater uptake of evidence-based behaviours. Across studies, factors supporting success included adequate time, access to technological resources, faculty preparation, and organizational support. Common barriers were limited infrastructure, faculty workload, and students’ initial resistance to active learning. Conclusions: Preliminary evidence suggests PBL enhances EBP-related competencies, but the current evidence base is small, heterogeneous, and lacks midwifery-specific studies. Rigorous comparative research using standardized outcomes and evaluating long-term practice impact is needed to establish optimal strategies for integrating PBL into nursing and midwifery education.